Development of Program Strengthen Capacity in Teamwork of Teacher in the Secondary Educational Service Area Office 32 - Rungrot, Pongsatron; Thummatasananon, Sutham (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objectives of the research article were 1) to study current conditions and desirable conditions of competency’s teamwork for teachers, 2) to develop the competency’s teamwork program on competency’s teamwork for teachers of the Secondary Educational Service Area Office 32. The sample group consisted of 207 administrators and teacher. Tools used in this research are questionnaires, structured interviews. Rating Scales and record the frequency, percentage, mean, standard deviation, index and rank the needs. The results of the research revealed that : 1. The current conditions and desirable conditions of competency’s teamwork. Current performance of the teamwork of teachers. The overall level and the high level in every aspect. The adverse conditions overall, the highest level. And found that the highest levels in all aspects. 2) Result of development the competency’s teamwork program Assessment of the suitability and feasibility of the program, capacity building teamwork of teachers Suitability is at a high level and the possibility is at the highest level.